Post-harvest Application and Physicochemical Properties of Jamun (Syzygium cuminii L.) - , Sankar M; , Rajesh G. K; , Prince M. V; , Sudheer K. P; , Sreeja R (Archives of Current Research International, 2024)
Jamun (Syzygium cuminii L.) is a subtropical fruit that comes under myrtaceae family originated from the Indian subcontinent. India is the second largest producer of jamun with an annual production of 2.1 million ton which contributes 15.4% of world production. Jamun is a highly perishable seasonal fruit (May–June). Hence, processing and preservation are essential to ensure the availability of its products throughout the year. Engineering and physicochemical properties of the fruit play a crucial role in the design and development of processing equipment, handling of food products and processing. The engineering properties of jamun fruit, including physical, mechanical, and frictional characteristics, were investigated in this study. Additionally, the physicochemical properties of jamun juice, such as pH, total soluble solids (TSS), acidity, total phenolic content, total anthocyanin content, antioxidant activity and vitamin C, were measured as per standard procedures. Jamun contains 80 percent pulp and nearly 20 percent seed. The physical properties of jamun fruit, including length, width, thickness, sphericity, bulk density, and porosity, were determined to be 22.22 mm, 21.93 mm, 20.99 mm, 0.947, 0.67g/, and 32.48%, respectively. The firmness of the fruit was measured as 1.09 N and co efficient of friction of the fruit for different materials such as stainless steel, plywood, cardboard and glass were determined to be 1.25, 1.28, 1.56, 1.98, respectively. The physiochemical properties like moisture, pH, TSS, acidity, specific gravity, total phenolic content, antioxidant activity, total anthocyanin content and vitamin c were found to be 85.33 % (wb), 3.12, 13.14%, 0.81, 0.9, 256.76 mg/100ml, 86%, 1281 mg/100ml and 16 mg/100ml, respectively. These properties highlight its significant potential as a functional food and raw material for various food processing applications.